Anatomical classification of advanced biliary tract cancer predicts programmed cell death protein 1 blockade efficacy - Huang, Lingli; Wang, Fang; Wang, Fenghua; Jiang, Qi; Huang, Jinsheng; Li, Xujia; Guo, Guifang (Frontiers in Pharmacology, 2024)
Background Immune checkpoint blockade (ICB)-based immunotherapy has inspired new hope for advanced biliary tract cancer (BTC) treatment; however, there are no prior studies that primarily focus on different anatomical types of unresectable BTCs reacting differently to ICB. Methods We retrospectively collected data on advanced BTC patients who received anti-programmed cell death protein 1 (anti-PD1) therapy from two affiliated hospitals of Sun Yat-Sen university. The effects of anti-PD1 were compared for different anatomical sites. The GSE32225 and GSE132305 datasets were used to further analyze differences in the immune microenvironments between intrahepatic cholangiocarcinoma (ICC) and extrahepatic cholangiocarcinoma (ECC). Results A total of 198 advanced BTC patients were enrolled in this study, comprising 142 patients with ICC and 56 with other cancer types (“Others” group), including ECC and gallbladder cancer. In the anti-PD1 treated patients, the ICC group (n = 90) achieved longer median progression-free survival (mPFS) (9.5 vs. 6.2 months, p = 0.02) and median overall survival (mOS) (15.1 vs. 10.7 months, p = 0.02) than the Others group (n = 26). However, chemotherapy did not show different effects between the two groups (mOS: 10.6 vs. 12.1 months, p = 0.20; mPFS: 4.9 vs. 5.7 months, p = 0.83). For the first-line anti-PD1 therapy, the ICC group (n = 70) achieved higher mOS (16.0 vs. 11.8 months, p = 0.04) than the Others group (n = 19). Moreover, most chemokines, chemokine receptors, major histocompatibility complex molecules, immunostimulators, and immunoinhibitors were stronger in ICC than ECC; furthermore, CD8+ T cells and M1 macrophages were higher in ICC than ECC for most algorithms. The immune differential genes were mainly enriched in antigen processing and presentation as well as the cytokine receptors. Conclusions This study shows that the efficacy of anti-PD1 therapy was higher in ICC than in other types of BTCs. Differences in the immune-related molecules and cells between ICC and ECC indicate that ICC could benefit more from immunotherapy.